OPTIMALISASI DEEP LEARNING PADA KEGIATAN KO-KURIKULER DI SEKOLAH DASAR - Ahmad Putra, Oktarian; Anggraeni Siwi, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the role of co-curricular activities in supporting the optimization of deep learning at SD N Sidorejo 03, Bendoasi, Sukoharjo, and identify challenges and solutions in its cultivation. Data were collected through observation, interviews, and documentation, with data validation using source and method triangulation. Data analysis was carried out using the Miles and Huberman interactive analysis model which includes three main stages, namely data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that co-curricular activities such as healthy and clean living, respecting differences, and living frugally and simply play a role in developing students' critical, creative, and collaborative thinking skills. Challenges faced include limited implementation time, lack of student focus, and resistance to changes in methods. Proposed solutions include more structured management of co-curricular activities, and increasing awareness of the importance of deep learning. This study provides insights for the development of a more effective curriculum in elementary education.